Progress and remaining challenges for cancer control in Latin America and the Caribbean. Issue 14 (October 2015) - Strasser-Weippl, Kathrin; Chavarri-Guerra, Yanin; Villarreal-Garza, Cynthia; Bychkovsky, Brittany L; Debiasi, Marcio; Liedke, Pedro E R; Soto-Perez-de-Celis, Enrique; Dizon, Don; Cazap, Eduardo; de Lima Lopes, Gilberto; Touya, Diego; Nunes, Joāo Soares; et al.
Summary: Cancer is one of the leading causes of mortality worldwide, and an increasing threat in low-income and middle-income countries. Our findings in the 2013 Commission in The Lancet Oncology showed several discrepancies between the cancer landscape in Latin America and more developed countries. We reported that funding for health care was a small percentage of national gross domestic product and the percentage of health-care funds diverted to cancer care was even lower. Funds, insurance coverage, doctors, health-care workers, resources, and equipment were also very inequitably distributed between and within countries. We reported that a scarcity of cancer registries hampered the design of credible cancer plans, including initiatives for primary prevention. When we were commissioned by The Lancet Oncology to write an update to our report, we were sceptical that we would uncover much change. To our surprise and gratification much progress has been made in this short time. We are pleased to highlight structural reforms in health-care systems, new programmes for disenfranchised populations, expansion of cancer registries and cancer plans, and implementation of policies to improve primary cancer prevention.